Influence of anchorage on flexural strength of beams strengthened with CFRP sheets - de Pina Ferreira, Mauricio; Honorato de Oliveira, Marcos; Lima Neto, Aarao Ferreira; Sales Tapajós, Luamim; Nascimento, Alex; Caires Freire, Marília (Revista ALCONPAT, 2018)
In order to evaluate the influence of anchorage on the flexural strength of beams strengthened with Carbon Fiber Reinforced Polymer (CFRP) sheets, the experimental results of 126 tests in the literature and of an unprecedented series with 4 reinforced concrete beams, tested by these authors, were analyzed. The parameters affecting the performance and the strength of the beams are evaluated, and the design criteria of fib Bulletin 14 (2001) and ACI 440-2R (2008) are discussed. It was observed that, even with auxiliary devices in the PRFC anchorage, premature failure is possible, and also that both theoretical recommendations lead to safe estimates, but excessively conservative in cases where the anchorage of the PRFC sheet is properly done.